ARTIFICIAL INTELLIGENCE TOOLS FOR JUNIOR HIGH SCHOOL STUDENTS IN ENGLISH LANGUAGE LEARNING CONTEXT - Sherly Eki Winanda; Wisma Yunita; Ira Maisarah (English Review: Journal of English Education, 2025)
With the rapid advancement of technology, Artificial Intelligence (AI) has become a key tool in education. This study investigates the types of AI used by students and their perspectives on AI in English language learning at state and private junior high schools in Rejang Lebong Regency. Using a quantitative approach, 235 students participated in a questionnaire with a four-point Likert scale. Data were analyzed using the Kolmogorov-Smirnov test, Levene’s test, one-way ANOVA, and mean interval scale. Findings showed that while most AI applications, including Quizziz, Kahoot, Grammarly, Google Translate, Google Classroom, and Duolingo, had no significant differences in usage (p > 0.05), Babbel and ChatGPT exhibited significant variations (p < 0.05), suggesting differences in adoption. ANOVA results indicated no significant difference in students' perspectives on AI (p = 0.137), with an overall positive perception. Educators can integrate AI tools like Babbel and ChatGPT for targeted language learning while using widely accepted applications such as Google Translate and Duolingo to enhance accessibility. Understanding students' shared perspectives on AI helps educators create more inclusive learning environments, optimizing technology’s role in language acquisition.